Performance Evaluation of Bio-CSTR for Biohydrogen Production from Palm Oil Mill Effluent (POME) - Nurdiah Rahmawati; Joni Prasetyo; Galuh Wirama Murti; Tyas Puspita Rini; Atti Sholihah; Era Restu Finalis; Semuel Patisenda (Program Studi Teknik Kimia, Universitas Pamulang, 2022)
Hydrogen production from biomass is a prospectus energy carrier. Biohydrogen so far only shares 8% of total hydrogen production Therefore, the production of biohydrogen still has to be increased for its contribution of the total required hydrogen, especially in Indonesia, which is a tropical country and rich in biomass. This research and development would utilize POME, Palm Oil Mill Effluent, as the substrate to produce biohydrogen. The utilization of POME will give added value and solve the environmental problem as well. Based on a modified existing bio-reactor, a bio–Continuous Stirred Tank Reactor (CSTR), the production of biohydrogen was successfully conducted at a scale of 1,000 dm3 working volume. The bio-CSTR worked with impellers in 4 different levels and the substrate flew laminarly and non-stagnant. As in the first test, biogas production from POME with the majority content of CH4, the pH and COD was measured to assess the quality of this POME utilization. The product was also analyzed, especially to monitor the existence of CH4 and to assure the product bio H2. Bio CSTR was applied in the method fed-batch system. POME and some additional nutrients were fed daily. The work was conducted at least for 2 weeks based on working planning. As the result, biohydrogen is still stable in duration 18 days operations, no CH4 exist. The pH was smaller at overflow POME, decreasing maximum, from 4.9 to 4.8. This condition was considered tolerable. The H2 concentration in gas product was reached 26% and stable at 12% until the end of the experiment.